2009
DOI: 10.2337/db09-0557
|View full text |Cite
|
Sign up to set email alerts
|

Immune Depletion With Cellular Mobilization Imparts Immunoregulation and Reverses Autoimmune Diabetes in Nonobese Diabetic Mice

Abstract: OBJECTIVEThe autoimmune destruction of β-cells in type 1 diabetes results in a loss of insulin production and glucose homeostasis. As such, an immense interest exists for the development of therapies capable of attenuating this destructive process through restoration of proper immune recognition. Therefore, we investigated the ability of the immune-depleting agent antithymocyte globulin (ATG), as well as the mobilization agent granulocyte colony–stimulating factor (GCSF), to reverse overt hyperglycemia in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 42 publications
6
68
1
Order By: Relevance
“…The rationale of using G-CSF in this study was to employ its immunoregulatory properties, including its ability to mobilise regulatory T cells, induce tolerogenic dendritic cells and shift cytokine phenotype from T-helper type 1 to type 2 [13,14]. Previously we demonstrated that G-CSF enhanced the efficacy of ATGmediated reversal of type 1 diabetes in the NOD mouse model, but as in the present study G-CSF monotherapy did not prevent or reverse disease [4]. Unfortunately, in the present study, we did not observe an enhancing effect when G-CSF was used in combination with AAT.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…The rationale of using G-CSF in this study was to employ its immunoregulatory properties, including its ability to mobilise regulatory T cells, induce tolerogenic dendritic cells and shift cytokine phenotype from T-helper type 1 to type 2 [13,14]. Previously we demonstrated that G-CSF enhanced the efficacy of ATGmediated reversal of type 1 diabetes in the NOD mouse model, but as in the present study G-CSF monotherapy did not prevent or reverse disease [4]. Unfortunately, in the present study, we did not observe an enhancing effect when G-CSF was used in combination with AAT.…”
Section: Discussionmentioning
confidence: 50%
“…Histology and immunohistochemistry Insulitis was evaluated and scored on pancreatic sections stained with haematoxylin and eosin, as described previously [4][5][6]. Briefly, the degree of lymphocytic infiltration in each islet was scored according to the following scale: 0, none; 1, peri-islet infiltrates; 2, <50% intra-islet infiltrates; 3, >50% intra-islet infiltrates.…”
Section: Insulin Tolerance Test (Itt)mentioning
confidence: 99%
See 3 more Smart Citations